'I do what a woman should do': a grounded theory study of women's menstrual experiences at work in Mukono District, Uganda. Issue 11 (20th November 2020) - Hennegan, Julie; Kibira, Simon P S; Exum, Natalie G; Schwab, Kellogg J; Makumbi, Fredrick E; Bukenya, Justine
Abstract : Menstrual health has received increasing recognition as an essential issue for public health and gender equality. A growing body of research has elucidated adolescent girls' menstrual needs and informed policy and practice responses. However, the experiences of adult women have received little attention, particularly in the workplace where many spend a significant proportion of their lives. To address this gap, we took a grounded theory approach to generate a nuanced understanding of working women's menstrual experiences, and the impact of menstruation on their work and health in Mukono District, Uganda. In-depth interviews were undertaken with 35 women aged 18–49. This included 21 women working in markets, 7 teachers and 7 healthcare facility workers. Frequent collaborative analysis sessions throughout data collection, coding of interview transcripts, and generation of participant, workplace, and category memos facilitated analysis. Our core category and underlying theory, ' being a responsible woman', underpinned women's experiences. ' Being responsible' meant keeping menstruation secret, and the body clean, at all times. These gendered expectations meant that any difficulty managing menses represented a failure of womanhood, met with disgust and shame. Difficulties with menstrual pain and heavy bleeding were excepted from these expectations and perceived as requiring compassion. Commercial menstrual products were expensive for most women, and many expressed concerns about the quality of cheaper brands. Workplace infrastructure, particularly unreliable water supply and cleanliness, was problematic for many women who resorted to travelling home or to other facilities to meet their needs. Menstruation presented a burden at work, causing some women to miss work and income, and many others to endure pain, discomfort and anxiety throughout their day. Our findings can inform norm and resource-focused responses to improve experiences and should provoke critical reflection on the discourse used in menstrual health advocacy in Uganda.